Determination of CMOD-force curves and R-curves in side-grooved single edge notched tensile (SENT) specimens in welded X42 pipeline steel. (June 2018) - Ameli, Iman; Asgarian, Behrouz; Lin, Meng; Agbo, Sylvester; Imanpour, Ali; Duan, Da-Ming; Cheng, Roger; Adeeb, Samer
Abstract: A comprehensive experimental project including tension and single edge notch tension (SENT) tests was carried out on 22 inch OD X42 welded pipeline steel to determine the mechanical properties and fracture toughness of the base and weld materials. In addition to traditional clip gauge measurements, digital image correlation (DIC) methodology was applied. Crack tip opening displacement (CTOD)-crack growth and crack mouth opening displacement (CMOD)-force curves were generated for SENT specimens subjected to monotonic tension loading using a multiple specimen technique. Significant differences were observed in the behavior of base metal and weld specimens. The evidence of fracture resistance measured from the weld metal specimens being lower than that from base metal specimens is important with respect to avoiding overestimation of R-curves in integrity assessment procedures. Additionally, the weld metal tolerated more force when the CMOD was less than 0.9 mm but the base metal tolerated more force after this point, while both CMOD-force curves reached a similar value of maximum force.